Low survival, high predation pressure present conservation challenges for an endangered endemic forest mammal. (May 2018) - Goldstein, Emily A.; Merrick, Melissa J.; Koprowski, John L.
Abstract: Knowledge of which population parameters and mortality risks contribute most to population decline and endangerment is necessary to develop informed and actionable conservation plans for threatened and endangered species (Rushton et al., 2006). The federally endangered Mount Graham red squirrel ( Tamiasciurus fremonti grahamensis ) is restricted to the Pinaleño Mountains, in southeastern Arizona, USA. The population is critically threatened with extensive habitat loss from fire as well as by an introduced non-native squirrel species, the Abert's squirrel ( Sciurus aberti ). Recovery is challenged by low survival and poor reproduction, such that the subspecies is functionally semelparous. We calculate survival rates and cause-specific mortality hazards from known-fate individuals to understand the impact of predation on survival and demography in this peripheral population. We document the lowest survival and highest rates of mortality in any population of North American red squirrels in both adult and juvenile age classes (mean annual survival: adults = 0.32, juveniles = 0.26). We attributed the majority of confirmed deaths to avian predation (adults 65%, juveniles 75%), and the daily hazard rate for avian predation was 15 times higher than for mammalian predation and 2 times higher than death from unknown causes. It is likely that the presence of an ecologically similar, non-native tree squirrel subsidizes a diverse avian predator guild, which includes two raptor species of conservation concern. In addition to efforts to remove the non-native Abert's squirrel, we recommend immediate forest restoration efforts in the long term, and habitat augmentation to increase structural complexity, cover, shelter, and food resources in the short term.